19 The Colonial Records of the State of Georgia§291, 296 (1910) - (:unkn) unknown (My University, 1773)
"That every Person liable llable to ap to appear and bear arms at any Exercise Muster or Training hereby appointed Pursuant to the directions of this Act Shall constantly keep and bring with them to Such Muster Exercise or Training one Gun or Musket fit for Service one Catridge Box with at least Nine Catridges filled with Good Gun owder and Ball that shall fit his Piece a horn or Flask containing at least aQuarter of a Pound of Gun Powder a shot Pouch with half a pound of Bulletts..."
Keywords: REQUIRED POSSESSION